Methods and Thoughts in the Islamic Theology - Muhammad Zaini (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
The discourse that has developed so far around Islamic theology includes the emergence of dominant theological currents due to political factors. Yet if it is explored more in-depth, freedom of thought (tafakkur) is one of the main factors. Based on this understanding, two issues need to be discussed in this paper: First, how are the various methods and patterns of thought that develop in the realms of Islamic theology; Second, what issues are the subject of debate in the realms of Islamic theology. The discussion is carried out by descriptive analysis based on relevant sources that are not limited in number. The discussion results show that the thought processes carried out by kalam scholars (mutakallimīn) have had a significant influence on the growth and development of Islamic theology. The arguments of the mind that were fertilized by Greek philosophy and other civilizations also played an important role in developing Islamic theology. Besides, the formation of more dominant schools is due to the different methods of thinking in explaining God, His oneness, and His attributes.